AB0045 MESENCHYMAL STEM CELLS INHIBIT THE ACTIVATED COMPLEMENT C5 BY CLUSTERIN IN LUPUS NEPHRITIS. (June 2019) - Ma, Haijun; Liu, Chang; Feng, Ruihai; Sun, Lingyun
Abstract : Background: Dysregulation of clusterin (CLU) and over-activated complement C5 were involved in the development and progression of lupus nephritis (LN). Allogeneic mesenchymal stem cells (MSCs) transplantation has achieved good clinical efficacy for refractory LN, however, the exact mechanisms remain to be elucidated. Objectives: To investigate the clinical effect of MSCs on SLE model mice (B6.lpr), and explore the mechanisms of MSCs inhibiting the activated complement C5 in vivo and in vitro . Methods: 26-week-old female B6.lpr mice were randomly allocated in three groups, which were given the following treatments, CTX (200mg/kg), MSCs (1 x 10 6 ), and an equal volume of PBS. 24 hours urine and peripheral blood were collected periodically. All mice were sacrificed at 40 weeks of age. Urine protein to creatinine ratio and plasma creatinine were quantified to evaluate renal disease. Levels of C3, soluble C5b-9 (SC5b-9), CLU, and anti-dsDNA antibody were determined in the plasma by ELISA. Histopathological evaluation of renal lesions was undertaken by HE, PAS, PASM and Masson staining under light microscopy. Podocyte foot processes were assayed by the transmission electron microscopy. Accumulation of immunocomplexes (IC), C3, C5b-9, and CLU were detected in renal specimens by immunofluorescence or immunohistochemistry. Expressions of CLU in MSCs were detected by real-time PCR and ELISA. MSCs-derived CLU was purified and functional analysis was performed accordingly. Results: Compared to the control mice, both proteinuria and plasma creatinine were significantly improved in each treatment group. Plasma C3 was significantly elevated in mice of MSCs and CTX groups. There were decline trends in plasma levels of anti-dsDNA and SC5b-9 in treated mice when compared to the control mice. Notably, plasma CLU was only significantly elevated in MSCs treated mice. Pathological analysis showed that the proliferation of glomerular cells and foot process fusion were significantly alleviated in MSCs treated mice. Immunofluorescence and immunohistochemistry showed that depositions of IC, C1q, C3 and C5b-9 were significantly decreased in the MSCs group, although the expression of CLU was obviously increased in these mice. Mechanistically, interferon-α promoted the secretion of functional CLU by MSCs in vitro . Conclusion: Allogeneic MSCs transplantation can effectively improve the clinical outcome of lupus mice. Possible mechanisms of MSCs might be related to inhibit the activated C5 via clusterin, which would be a potential treatment target in the future. Reference: [1] Harris CL, et al. Mol Immunol. 2018 Disclosure of Interests: None declared